KEANEKARAGAMAN FITOPLANKTON DI ALIRAN SUMBER AIR PANAS CONDRODIMUKO GEDONGSONGO KABUPATEN SEMARANG (Life Science, 2013)
Condrodimuko Gedongsongo is one of the hot water sources where placed at north of Ungaran mountain in Kabupaten Semarang. The hot temperature and mineral content of the hot waters only tolerant phytoplankton that can be survive in this condition. The aim of this research was to know the species diversity of phytoplankton in the flow of hot waters in Condrodimuko Gedongsongo this condition. Selected sampling purpossive sampling at three stations, each station do three sampling period. The species number and the individual number of the phytoplankton were taken as data to conclude the diversity species of phytoplankton using Shannon-Wiener method. The result of the research was nine species of phytoplankton were found there are Cladopora sp, Gonatozygon sp, Microspora sp, Oscillatoria sp, Phormidium sp, Protococcus sp, Tribonema sp, Diatom sp dan Ophiocytium sp. The result of analysis on phytoplankton diversity of hot water sources at the Condrodimuko Gedongsongo Kabupaten Semarang the value 2,09 and is one of high diversity.